Quad: Origin and Evolving Dynamics - Srabani Roychoudhury (Journal Of Global Strategic Studies, 2021)
Quad is not a formal treaty, and for its members, it is not the only platform in Asia. It has brought like-minded maritime democracies together to create a Free and Open Indo-Pacific. It has responded to disaster crises and the pandemic more promptly than China’s aggressive moves in the Indo-Pacific region. This article aims to understand the origin of ‘the Quad’ referred to as Quad 1.0 and its failure in 2007 and re-emergence of it as Quad 2.0. Quad 2.0 is further divided into the pre-pandemic Quad 2.1 and pandemic onset Quad 2.2. This article articulates the trajectory that Quad has traversed to reach Summit level meetings and its pursued agenda. The latest development in this arena is forming a trilateral agreement between Australia, the United States and the United Kingdom (AUKUS). This article questions the role of Quad in view of the formation of AUKUS and draw on its implications. It concludes that Quad has faltered in answering the security concern, paving the way for AUKUS. Quad’s role is likely to turn towards a developmental paradigm of ‘productive global public good’. In the long run, this will help create an equitable cohesive region and realize the ambition of a Free and Open Indo-Pacific.